Delayed Transfer of the Extensor Carpi Radialis Brevis Branch of the Radial Nerve to the Anterior Interosseous Nerve for Restoration of Thumb and Index Finger Flexion: Case Report - Salomão, Renan; de Oliveira, Jairo Porfírio, Jr; Junger, Carolina Fernandes; Soares Ricardo, Luiz Cezar, Jr; de Lima, Carlos Roberto; Acioly, Marcus Andre (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
High median nerve injuries (HMNIs) are rare lesions involving the upper extremities and affect the median nerve from its origin to the emergence of the anterior interosseous nerve (AIN). Proximal reconstruction has long been considered the gold standard in treating HMNI, but thumb and index flexion and pinch and grip weakness are consistently not recovered. We report the surgical results of a patient affected by an HMNI with partial spontaneous recovery after a gunshot wound. AIN function was successfully restored in a delayed fashion by transferring the radial nerve branch to the extensor carpi radialis brevis to the AIN.
Keywords: anterior interosseous nerve; finger flexion reconstruction; high median nerve injury; nerve transfer